Association between intake of antioxidants and pancreatic cancer risk: a meta-analysis. (2nd October 2016) - Chen, Jiamin; Jiang, Wuxia; Shao, Liming; Zhong, Dandan; Wu, Yihua; Cai, Jianting
Abstract: We conducted a meta-analysis to systematically evaluate the association between antioxidants intake and pancreatic cancer risk. Relevant articles were retrieved from PUBMED and EMBASE databases and standard meta-analysis methods were applied. Finally a total of 18 studies were included. Comparing the highest with lowest categories, higher dietary intakes of selenium, vitamin C, vitamin E, β-carotene and β-cryptoxanthin were significantly associated with reduced pancreatic cancer risk (for selenium, pooled OR = 0.47, 95%CI 0.26–0.85; for vitamin C, pooled OR = 0.68, 95%CI 0.57–0.80; for vitamin E, pooled OR = 0.70, 95%CI 0.62–0.81; for β-carotene, pooled OR = 0.74, 95%CI 0.56–0.98; for β-cryptoxanthin, pooled OR = 0.70, 95%CI 0.56–0.88). Lycopene intake was marginally associated with pancreatic cancer risk (pooled OR = 0.85, 95%CI 0.73–1.00), while no significant association was observed for α-carotene, lutein and zeaxanthin. In summary, higher dietary intake of selenium, vitamin C, vitamin E, β-carotene and β-cryptoxanthin was inversely associated with pancreatic cancer risk.